Metal Material, Properties and Design Methods of Porous Biomedical Scaffolds for Additive Manufacturing: A Review - Lv, Yuting; Wang, Binghao; Liu, Guohao; Tang, Yujin; Lu, Eryi; Xie, Kegong; Lan, Changgong; Liu, Jia; Qin, Zhenbo; Wang, Liqiang (Frontiers in Bioengineering and Biotechnology, 2021)
Design an implant similar to the human bone is one of the critical problems in bone tissue engineering. Metal porous scaffolds have good prospects in bone tissue replacement due to their matching elastic modulus, better strength, and biocompatibility. However, traditional processing methods are challenging to fabricate scaffolds with a porous structure, limiting the development of porous scaffolds. With the advancement of additive manufacturing and computer-aided technologies, the development of porous metal scaffolds also ushers in unprecedented opportunities. In recent years, many new metal materials and innovative design methods are used to fabricate porous scaffolds with excellent mechanical properties and biocompatibility. This article reviews the research progress of porous metal scaffolds, and introduces the additive manufacturing technologies used in porous metal scaffolds. Then the applications of different metal materials in bone scaffolds are summarized, and the advantages and limitations of various scaffold design methods are discussed. Finally, we look forward to the development prospects of additive manufacturing in porous metal scaffolds.